Clinically‐suspected cast nephropathy: A retrospective, national, real‐world study. Issue 11 (26th August 2020) - Szabo, Agoston G.; Thorsen, Jonathan; Iversen, Katrine F.; Hansen, Charlotte T.; Teodorescu, Elena M.; Pedersen, Simon B.; Flæng, Simon B.; Strandholdt, Casper; Frederiksen, Mikael; Vase, Maja Ø.; Frølund, Ulf C.; Krustrup, Dorrit; et al.
Abstract: Presentation with severe acute kidney injury due to cast nephropathy (CN) is a medical emergency in multiple myeloma (MM), with high risk of dialysis‐dependent renal failure and death. Accrual of patients with CN into interventional studies is difficult, while phase III trials exclude patients with severe renal insufficiency. Real‐world data are warranted. We assessed 2252 patients from the population‐based Danish Multiple Myeloma Registry (DMMR) who were diagnosed between 2013 and 2017. We identified 204 patients with clinically‐suspected CN, defined as serum creatinine concentration >177 μmol/L and serum free light chain (sFLC) concentration >1000 mg/L at the time of diagnosis. The median age was 72 years. Thirty‐one percent of patients presented with dialysis‐dependent renal failure. Kidney biopsies were performed in 19% of patients and showed CN in 74% of cases. Despite prompt initiation of bortezomib‐based therapy in 94% of patients, 33% of patients died in the first year after diagnosis. Compared with the rest of the patients in the DMMR with symptomatic MM, patients with clinically‐suspected CN had worse overall survival (OS) irrespective of transplant eligibility. Achievement of renal recovery was associated with deep reductions of involved sFLC. Achievement of very good partial response or better in the first line of therapy and/or deep reduction of involved sFLC at 3 months after initiation of therapy were associated with superior OS. In conclusion, MM patients presenting with clinically‐suspected CN have an alarmingly high one‐year mortality when treated with current standards of care. Early and deep hematologic response is crucial for survival.